Eastern sea spreading and the development of Phu Khanh basin: updated from the results of new 2D seismic interpretation - Bách, Hoàng Việt; Hưng, Nguyễn Du; Cảnh, Đào Viết; Tâm, Nguyễn Minh; Việt, Lê Tuấn; Hoài, Tạ Thị Thu (Vietnam Journal of Earth Sciences, 2014)
Before 2008, on the Phu Khanh basin area, the seismic surveys are mainly carried out on the western edge. Therefore, the characteristics of stratigraphic, structure and tectonic evolution, especially the eastern boundary of the basin has not been clarified. From the years of 2008 - 2010, the 2D seismic surveys had been conducted in the east part of Phu Khanh basin. The results of new seismic interpretation help us to understand much more about the characteristics of stratigraphy, structure, tectonic and the history of evolution of this basin. On the structural map of east 257 sea area of Viet Nam, the Phu Khanh basin includes the area of petroleum contract blocks from 121 to 126 and from 144 to 151. The eastern boundary of basin is the new oceanic crust domain with the years from 32 to 16 million. The southwestern boundary of basin is Tuy Hoa shear zone, Cuu Long and Nam Con Son Basin. The west of basin is Kontum massif and the northwest is Song Hong basin and Tri Ton uplift. The results of analyzing 2D seismic show that the Phu Khanh basin is constituted by Pre-Cenozoic basement and Cenozoic sediments. The lithological component of Pre-Cenozoic basement is heterogeneous. The north part of basin is characterized by metamorphic, intrusive and volcanic rocks of Kontum massif. The south part of basin is characterized by sedimentary rocks and volcanic and intrusive rocks of late Mesozoic pluton arc in Da Lat zone. The Cenozoic sediment is divided into 3 parts: Oligocene - lower Miocen, middle - upper Miocene and Pliocene - Quaternary. The first part were formed due to the East Sea spreading activities. The second part were formed by the meridian 110o fault system activities. The final part were formed by mechanism of thermal subsidence. The characteristics of stratigraphy, structure and evolution of Tuy Hoa shelf, Phu Yen trough and Khanh Hoa ridge are diferrent. In this paper content, the authors focus on analyzing the detail of tectonic evolution of strike slip zones Quy Nhon-Nam Hoang Sa, Tuy Hoa, meridian 110o fault and East Sea spreading activities, also assess the their influences on formation and evolution of Phu Khanh basin.